A joint analysis of the KOSPI 200 option and ODAX option markets dynamics - Ji Cao; Wolfgang Karl Härdle; Julius Mungo (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
As a function of strike and time to maturity the implied volatility estimation is a challenging task in financial econometrics. Dynamic Semiparametric Factor Models (DSFM) are a model class that allows for the estimation of the implied volatility surface (IVS) in a dynamic context, employing semiparametric factor functions and time-varying loadings. Because financial asset volatilities move over time, across assets and over markets, this paper analyses volatility interaction between German and Korean stock markets. As proxy for the volatility, factor loadings series derived from a DSFM application on option prices are employed. We examine volatility transmission between the markets under the vector autoregressive (VAR) model framework. Our results show that a shock in the volatility of one market may not translate directly into greater uncertainty in another market and it is unlikely that portfolio investors can benefit from diversification among these markets due to cointegration.
Keywords: C14; G12; 330; implied volatility surface; dynamic semiparametric factor model; VAR; cointegration; Börsenkurs; Volatilität; Internationaler Preiszusammenhang; Spillover-Effekt; Faktorenanalyse; Kointegration; Schätzung; Aktienmarkt; Deutschland; Südkorea